Inadvertent Rupture of a Silicone Breast Implant during Fat Grafting: Surgical and Radiological Findings. Issue 6 (June 2020) - Stewart, Christopher N.; Heinrich, Cherrie A.
Abstract : Summary: Autologous fat grafting is a common, relatively safe procedure for breast augmentation and reconstruction. The most commonly reported complications tend to be fat necrosis and oil cysts. The incidence of rare events, such as breast implant rupture, is likely underreported. Here we present the case of a patient who underwent fat grafting and sustained implant rupture with injection of fat within the silicone implant. She complained of her implant changing shape and magnetic resonance imaging (MRI) showed classic signs of implant rupture (linguini sign). At the time of surgery however, fat was surprisingly found to be within the implant itself. To our knowledge this finding has yet to be reported. Here we review the radiologic and surgical findings of implant rupture following fat grafting and present some suggestions to prevent this occurrence and ensure safe, aesthetically pleasing outcomes.